Pengembangan Bahan Ajar Teks Debat Berbasis Sosial Politik Siswa Kelas X SMA - Syauqi, Muhammad Abrar; Ali, Ali; Kartika, Rika (Medan Resource Center, 2024)
This study aimed to develop a socio-political-based debate text learning module for class X SMA. Following the 3D model (Define, Design, and Development) proposed by Thiagarajan, the module underwent validation by four experts, including two material experts and two design experts. Utilizing a Likert scale questionnaire, the validation sheet assessed material and design aspects. The material's quality received an average score of 3.60 from the first material expert, deemed